Testing the effects of an oral contraceptive on two plantation rodent pests, the striped mouse (Rhabdomys pumilio) and vlei rat (Otomys irroratus) : a laboratory study - Van Wyk, Ernita (Stellenbosch : Stellenbosch University, 2012)
Thesis project (M. Sc.) -- University of Stellenbosch, 1997.